Short-Term Exposures to Ambient Air Pollution and Risk of Recurrent Ischemic Stroke - Wing, Jeffrey J. (Environ Res, 2016)
OBJECTIVE: To investigate the association between short-term changes in ambient pollution (particulate matter <2.5μm in aerodynamic diameter (PM(2.5)) and ozone (O(3))) and the risk of recurrent ischemic stroke among individuals living in a bi-ethnic community. METHODS: We identified recurrent ischemic stroke cases from the population-based Brain Attack Surveillance in Corpus Christi (BASIC) project between 2000 and 2012. Associations between PM(2.5) (mean 24-hour) and O(3) (maximal 8-hour) levels, measured on the previous day, and odds of ischemic stroke were assessed using a time-stratified case-crossover design and modeled using conditional logistic regression. RESULTS: There were 317 recurrent ischemic strokes after excluding 41 strokes that occurred on days with missing air pollution data. Mean age was 72 years (SD=12) and median time to stroke recurrence was 1.1 years (IQR: 0.2-2.8 years). Median levels of PM(2.5) and O(3) over the study period were 7.7 μg/m(3) (IQR: 5.6-10.7 μg/m(3)) and 35.2 ppb (IQR: 25.0-46.1 ppb), respectively. We observed no associations between previous-day PM(2.5) and O(3) and odds of recurrent stroke (OR=0.95 per 10μg/m(3) of PM(2.5), 95% CI: 0.71-1.28 and OR=0.97 per 10ppb of O(3), 95% CI: 0.87-1.07) after adjusting for ambient temperature and relative humidity. Co-adjustment of both pollutants did not change the results. CONCLUSION: We found no evidence of associations between previous-day air pollution levels and recurrent ischemic stroke. Research on the influence of air pollutants on risk of stroke recurrence is still in its infancy, and more research is necessary in studies that are adequately powered to understand the relation.